ADSORPSI Hg(II) DENGAN ADSORBEN ZEOLIT MCM-41 TERMODIFIKASI - Sutardi Sutardi; Sri Juari Santosa; Suyanta Suyanta (Kaunia: Integration and Interconnection Islam and Science, 2014)
Synthesis of MCM-41 through hydrothermal process toward the mixture of 7.52 g Na2SiO3 and 2.28 g cethyltrimethylammonium bromide (CTAB) in 19 ml H2O adjusted at pH 10 by using H2SO4 solution 1 M has been done. The mixture was continuously stirred for 2 h at room temperature, moved to autoclave and proceeded hydrothermally at 150oC for 36 h. The solid product was filtered, washed, dried in oven at 80oC for 24 h, and then calcined at 550oC for 6 h. While, for synthesis of NH2-MCM-41, mixture of 1,0 gr MCM-41 and 2,0 mL (3-aminopropyl) trimethoxysilane (APTMS) was refluxed for 24 h with 100 mL toluene. The solid product was filtered off and washed with toluene and ethanol respectively and dried in oven at 50oC for 2 h. The solid product was characterized by infrared spectrophotometry, X- ray diffraction, TEM method, and sorption N2. The results of FTIR analysis showed the presence of Si-OH and Si-O-Si groups in the structure of MCM-41 and NH2-MCM-41. The existence of amino propyl functional groups was observed in the spectra NH2-MCM-41 showed the anchoring process against MCM-41 has been successfully carried out. The pattern of X-ray diffractgram and TEM image results for MCM-41 and NH2-MCM-41 showed a uniform hexagonal pore structure. The results of the analysis of N2 gas fisisorpsi by BET method showed that after anchoring process, the size of the surface area, pore diameter, and total pore volume decreases. The synthesized MCM-41 and NH2-MCM-41 were applied as adsorbent of Hg(II) in aqueous solution at pH 4. Adsorption of Hg(II) using  MCM-41 followed the first order mechanism with value of k1 1.73 x 10-3 minute-1, while adsorption of Hg(II) using NH2-MCM-41 fit well the second order mechanism with value of k2  3.97 x 10-5  (g/mol.minute). NH2-MCM-41 possesed better adsorption capacities, i.e. 63,29 mg/g (3,16 x 10-4  mol/g) than MCM-41, i.e. 14,21 mg/g (7,09 x 10-5 mol/g).